Frequency, distribution, and immunomorphologic characteristics of peripheral T-cell lymphoma, not otherwise specified in a tertiary care center in Southern India - Archana Lakshmanan; Deeksha Sikri; Sushama Patil; Ann Kurian; S Annapurneswari; Sheila Nair (Wolters Kluwer Medknow Publications, 2018)
Aims: In world literature, Peripheral T-cell lymphomas (PTCLs) constituted about 12% of non-Hodgkin's lymphomas (NHL) of which PTCL not otherwise specified (NOS) was the most common subtype. This study was undertaken to ascertain the frequency and to assess the morphologic and immunophenotypic characteristics of PTCL, NOS over a period of 5 years in a tertiary care referral center in Southern India. Materials and Methods: Slides and blocks of all PTCL, NOS were retrieved, and a detailed morphologic and immunophenotypic study using a wide panel of antibodies was done. Results: During this study, NHL constitutes 77.61% of all lymphomas. PTCL formed about 12.55% (251 cases) of all NHL. PTCL NOS was the most common subtype (30.68%). The most common site of involvement was lymph nodes (75%) followed by extranodal sites such as soft tissue (8.33%), gastrointestinal tract including oral cavity (6.67%), nasal cavity (5%), central nervous system (1.67%), lung (1.67%), and spleen (1.67%). PTCL, NOS showed a broad morphologic spectrum and had varied morphologic patterns with some mimicking reactive hyperplasia and some mimicking known type of T-cell lymphomas, B-cell lymphomas, and Hodgkin's lymphoma. Conclusions: PTCL, NOS constituted about 30.68% of all PTCLs in our institution during a 5-year period and was the second most common type of PTCL. Immunophenotyping using a wide panel of T-cell antibodies is necessary to distinguish PTCL, NOS from other lymphomas which they mimic, as they are known to carry a worse prognosis.